Análisis del impacto del sistema de riego Carrizal Chone primera etapa (SCCHOPE) en el desarrollo productivo agrícola en el área de influencia de la Provincia de Manabí periodo 2012-2014 - Bravo Cobeña, Carmen Xiomara (2016)
In this research , the application of agricultural productive development policies are analyzed in conjunction with irrigation policies by the GADP of Manabí, in the 2012-2014 triennium , after which he was awarded the competition irrigation and drainage to from 2011 ; specifically , the impact they have caused in an agricultural area , where the most impressive irrigation infrastructure in the province until the current date. Based on the analysis improvements are proposed from the local reality, with regard to agricultural production planning with which seeks the development of renewed processes and innovative in managing new powers aimed at a change of the productive matrix and integral development Manabí sustainable rurality.